2022
DOI: 10.3389/fnut.2022.983038
|View full text |Cite
|
Sign up to set email alerts
|

The impact of geriatric nutritional risk index on esophageal squamous cell carcinoma patients with neoadjuvant therapy followed by esophagectomy

Abstract: BackgroundThe Geriatric Nutritional Index (GNRI) has been indicated as a nutritional index which is highly associated with complications and mortality in older hospitalized patients. Moreover, early studies had suggested that GNRI is a potential prognostic indicator for some malignances. However, the prognostic value of GNRI in esophageal squamous cell carcinoma (ESCC) patients underwent neoadjuvant therapy followed by esophagectomy remains elusive.Materials and methodsThis retrospective study incorporated 373… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A positive correlation emerged between GNRI scores and GOS scores(P < 0.001), indicating a nutritional status may be signi cantly associated with recovery and long-term outcomes in brain abscess patients. Several studies also have demonstrated a correlation between elevated malnutrition risks and adverse clinical outcomes in geriatric patients [27,31]. It can be seen that in the process of diagnosis and treatment of geriatric diseases, the assessment of nutritional status cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation emerged between GNRI scores and GOS scores(P < 0.001), indicating a nutritional status may be signi cantly associated with recovery and long-term outcomes in brain abscess patients. Several studies also have demonstrated a correlation between elevated malnutrition risks and adverse clinical outcomes in geriatric patients [27,31]. It can be seen that in the process of diagnosis and treatment of geriatric diseases, the assessment of nutritional status cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI is a valuable tool for assessing sarcopenia incidence, mortality in hospitalized older patients, and various postoperative outcomes. [11][12][13] Additionally, this index has shown high prognostic value in various geriatric conditions, such as cancer, heart failure, and diabetes mellitus. [13][14][15] However, whether the GNRI could serve as a valuable prognostic indicator in older patients with hip fractures who underwent surgery has not been determined.…”
Section: All Data Generated or Analyzed During This Study Are Include...mentioning
confidence: 99%
“…These complications further lead to poor prognosis, including poor wound healing, increased infection rates, impaired tolerance to therapy, increased complications related to disease progression and therapy, delayed recovery with increased length of stay during hospitalization, reduced QoL, and, eventually, increased mortality. [14,15] During the coronavirus disease 2019 (COVID-19) pandemic, the important role of malnutrition in worsening risk of infection and disease outcomes has been unfortunately confirmed to be also a major component of disease burden in acute, infectious conditions, also in the presence of obesity. [16,17] Hospitalized patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (COVID-19) are at nutritional risk, [18] and nutritional management can significantly improve patient outcomes.…”
Section: Nutrition Health and Disease: A Fundamental Relationshipmentioning
confidence: 99%